Application of Positron Emission Particle Tracking (PEPT) to measure the bubble-particle interaction in a turbulent and dense flow. (1st September 2020) - Sommer, A.-E.; Ortmann, K.; Van Heerden, M.; Richter, T.; Leadbeater, T.; Cole, K.; Heitkam, S.; Brito-Parada, P.R.; Eckert, K.
Graphical abstract: Highlights: The effect of turbulence on bubble-particle interactions was studied with PEPT. A new tracer coating method was developed to mimic fluorescent PMMA spheres. An upstream grid generated well-defined turbulence in the water channel. Bubble-particle interaction were measured in an opaque flow. The particles residence time provided insight into the bubble-particle interaction. Abstract: In a flotation cell, turbulence influences the motion of solid particles relative to the bubble surface, and, thus, affects the recovery rate. But, the impact of turbulence on the probability of a bubble-particle aggregation is still difficult to measure, especially in a dense flow. Therefore, the focus of this work was to apply Positron Emission Particle Tracking (PEPT) as a method to investigate the effect of turbulence on the particle movement and bubble-particle interaction in an opaque flow. Single air bubbles ( d b = 2 . 5 mm ) were generated on a needle in a water flow channel. Upstream, a grid produced an isotropic turbulent flow with 5% to 15% turbulence intensity and a Kolmogorov microscale of 20 µm. Depending on the distance to the grid, the flow near the captive bubble ( R e b = 450 ) was characterized by eddies of different length scales and magnitude with tomographic Particle Image Velocimetry (PIV). The solid suspension contained up to 0.3% polymethylmethacrylate (PMMA) particles ( d p = 200 – 400 μ m ) and up to six radiolabelled particles ( d p = 300 – 400 μ m ) coated with PMMA. The trajectories of the labelled particles were used to determine the average particle distribution in the turbulent field and describe the bubble-particle interactions. These results provide valuable information on the applicability of PEPT in turbulent and dense flow fields as well as on particle trajectories close to bubbles, enhancing our understanding of key flotation phenomena.